Overweight and Obesity Among Children Between 9.12 years "crosssectional study" - Dr.Raghad Abdul Jabbar Mahdi; Dr.Omar Saad Tawfeek Al.Azzawi; Dr.Ali Qais Abdulkafi (Genius Journals, 2023)
"Overweight" technically refers to an excess of body weight, whereas "obesity" refers to an excess of fat.Childhood obesity is a growing problem and an increasing public health concern in the developed countries. Even more worrying is the increasing prevalence of obesity in developing countries. Childhood obesity is a well-recognized problem all over the world. Obesity can cause other medical problems in childhood, adolescence and adulthood.
Keywords: childhood; obesity; Body Mass Index; age